Fragile landscapes, fragile civilizations: how climate determined societies in the pre-Columbian south Peruvian Andes - Mächtle, Bertil; Eitel, Bernhard (Catena, 2013)
This paper presents alternating periods of geo-ecological fragility and stability in a highly sensitive environmental setting: the desert-margin area of southern Peru (14.5° S). There, we have to state that fragility was dominantly triggered by climatic changes, which induced several oscillations of the desert margin. During the mid-Holocene, the study area received the Holocene maximum of precipitation, soil formation occurred and the desert retreated, as loess-paleosoil formation documents. In contrast, the Titicaca region further south-east experienced extreme drought at that time. This regional antagonism between humid and dry conditions was a result of meridional shifts in moisture transport across the Andes and occurred also during pre-Columbian times. Considering a coincidence between environmental and cultural changes, we state that success and decline of civilizations were dominated by hydrological oscillations, triggering fertility as well as a critical loss of natural resources. Fragile periods, i.e. periods of geomorphological activity, occurred contemporaneous with cultural transitions. In response to spatial changing resources cultural foci were shifted. So, the success of pre-Columbian civilizations was closely coupled to areas of geo-ecological favorability, which were directly controlled by distinct regional impacts of large-scale circulation mechanisms, including El Niño-Southern Oscillation (ENSO). This spatial view on non-uniform environmental and cultural changes has not been thoroughly considered before. Therefore, for the first time this paper offers geomorphological evidence for diachronous Andean (agri-)cultural development, which was geographically determined.
Available online 20 February 2012
Gesehen am 11.06.2021